Decrease in CD38+ TH2A cell frequencies following immunotherapy with house dust mite tablet correlates with humoral responses. Issue 8 (15th May 2021) - Luce, Sonia; Batard, Thierry; Bordas‐Le Floch, Véronique; Le Gall, Martine; Mascarell, Laurent
Abstract: Background: In line with evidence for a role of pathogenic TH2A in seasonal allergies, we previously showed that individuals suffering from food allergy exhibited a decrease in circulating TH2A cells following multi‐food immunotherapy. Herein, we aim to confirm the decline of TH2A cells in individuals undergoing house dust mite immunotherapy (HDM‐AIT) and extend our observation to a new subset of CD38 expressing activated TH2A cells. Methods: The frequencies of TH2A and CD38 + TH2A cells were analysed by flow cytometry in blood cells from 182 Japanese HDM‐allergic individuals included in a 1‐year clinical trial assessing the efficacy of HDM tablets. Interrelationship between these cellular responses and humoral mite‐specific IgE and IgG4 levels was further explored. Results: A decrease in TH2A cells was observed in both active and placebo groups. Interestingly, CD38 + TH2A cell frequencies significantly decreased only in active groups. In younger individuals (16–30 years), both TH2A and CD38 + TH2A cells were significantly reduced in active groups but not in the placebo group. Significant inverse correlations were observed in the course of HDM‐AIT between changes in TH2A or CD38 + TH2A frequencies and IgG4 antibody levels. Conclusions: We confirm the value of monitoring TH2A cell frequencies in allergic individuals and extend this observation to perennial allergy to HDM. We highlight the interest of CD38 to better identify the subset of TH2A cell down‐regulated by AIT. Finally, correlated cellular and humoral responses observed in immunoreactive individuals stress that coordinated pathways occur in the adaptive responses during AIT. Abstract : Individuals suffering from house dust mite allergy exhibited a decrease in circulating CD38 + TH2A cells following 1‐year HDM tablet immunotherapy. Inverse correlations observed between changes in CD38 + TH2A frequencies and IgG4 or IgE antibody levels highlight correlated cellular and humoral responses and emphasize that coordinated pathways occur in adaptive responses during AIT.